Hubungan Pemakaian Alat Ortodontik Cekat dengan Status Kebersihan Gigi dan Mulut Siswa SMA Kristen 1 Tomohon - Rambitan, Wulan K. D.; Mintjelungan, Christy N.; Anindita, Pritartha S. (e-GiGi, 2019)
Abstract: Fixed orthodontic devices are the most commonly used orthodontic appliances in the community especially adolescent because they have become an important part of lifestyle. Albeit, users of fixed orthodontic appliances do not realize that fixed orthodontic appliances could become a risk factor for poor dental and oral hygiene. This study was aimed to determine the relationship between the use of fixed orthodontic devices and the dental and oral hygiene status of students at SMA Kristen 1 Tomohon (senior high school). This was an analytical observational study with a cross sectional design. Subjects were 43 students who used fixed orthodontics appliances obtained by using total sampling method. The results showed that most subjects used fixed orthodontic appliance for less than one year (58.1%). Moreover, the dental and oral hygiene status of most subjects were in the moderate category. The Chi-square showed a p-value of 0,060 for the relationship between the use of fixed orthodontic devices and the dental and oral hygiene status. Conclusion: There was no significant relationship between the duration of use of fixed orthodontic devices and the dental and oral hygiene status of students at SMA Kristen 1 TomohonKeywords: fixed orthodontic appliances, oral hygiene, adolescentsÂ Abstrak: Alat ortodontik cekat merupakan peralatan ortodontik yang paling sering dipakai oleh masyarakat khususnya remaja karena sudah menjadi bagian dari gaya hidup. Namun pemakai alat ortodontik cekat tidak menyadari bahwa alat ortodontik cekat merupakan faktor risiko terganggunya kebersihan gigi dan mulut. Penelitian ini bertujuan untuk mengetahui hubungan pemakaian alat ortodontik cekat dengan status kebersihan gigi dan mulut siswa SMA Kristen 1 Tomohon. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Subyek penelitian yaitu 43 siswa yang memakai alat ortodontik cekat yang diperoleh dengan metode total sampling. Hasil penelitian menunjukkan pemakaian alat ortodontik cekat terbanyak yaitu di bawah satu tahun (58,1%) dan status kebersihan gigi dan mulut berada dalam kategori sedang. Hasil uji Chi-square terhadap hubungan antara pemakaian alat ortodontik cekat dengan status kebersihan gigi dan mulut subyek penelitian mendapatkan nilai p=0,060. Simpulan: Tidak terdapat hubungan bermakna antara lama pemakaian alat ortodontik cekat dengan status kebersihan gigi dan mulut siswa SMA Kristen 1 Tomohon.Kata kunci: alat ortodontik cekat, kebersihan gigi dan mulut, remaja